2012
DOI: 10.1111/j.1467-789x.2011.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and mixed treatment comparison of pharmacological interventions for the treatment of obesity

Abstract: The study aims to compare anti-obesity interventions in a single evidence synthesis framework. Electronic databases were searched for randomized controlled trials of orlistat, rimonabant or sibutramine reporting weight or body mass index (BMI) change from baseline at 3, 6 or 12 months. A mixed treatment comparison was used to combine direct and indirect trial evidence. Ninety-four studies involving 24,808 individuals were included; 83 trials included data on weight change and 41 on BMI change. All results are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 26 publications
4
42
0
1
Order By: Relevance
“…218,226 The role of intentional weight loss in obesity as a means of preventing CVD has been the subject of multiple previous studies and reviews 218,219,222,[226][227][228][229] and is beyond the scope of this document. The recent 2013 AHA/ACC/The Obesity Society "Guideline for the Management of Overweight and Obesity in Adults" underlines the importance of the prevention and treatment of overweight and obesity on risk factors for CVD and type 2 diabetes mellitus, as well as CVD morbidity and mortality, but did not have specific comments on the prevention of HF or treatment of obesity in patients with HF.…”
Section: Treatment Of Obesity In Patients Without Established Hf and mentioning
confidence: 99%
See 1 more Smart Citation
“…218,226 The role of intentional weight loss in obesity as a means of preventing CVD has been the subject of multiple previous studies and reviews 218,219,222,[226][227][228][229] and is beyond the scope of this document. The recent 2013 AHA/ACC/The Obesity Society "Guideline for the Management of Overweight and Obesity in Adults" underlines the importance of the prevention and treatment of overweight and obesity on risk factors for CVD and type 2 diabetes mellitus, as well as CVD morbidity and mortality, but did not have specific comments on the prevention of HF or treatment of obesity in patients with HF.…”
Section: Treatment Of Obesity In Patients Without Established Hf and mentioning
confidence: 99%
“…In this study, the intervention group did not have weight loss, and there was no significant difference between the intervention and control groups in terms of metabolic, biomarker, or functional parameters. 227,240 In both studies, the intervention groups had a mean BMI >35 kg/m 2 . Neither study reported adverse events, however, suggesting that monitored, healthy dietary intervention programs aiming to achieve weight loss are safe in obese patients with HF.…”
Section: Dietary Interventionmentioning
confidence: 99%
“…10,11,13 Past pharmaceutical approaches have been equally disappointing, both in terms of modest treatment effects and unacceptable side effects. 14,15 At present, the most successful treatments for obesity are surgical procedures, still with limited application for most obese and overweight people. 14,16 The classic twin adoption studies of Stunkard showed that both fatness and thinness were highly heritable and not influenced by the adopting family members' adiposity.…”
Section: Background and Aimsmentioning
confidence: 99%
“…14,15 At present, the most successful treatments for obesity are surgical procedures, still with limited application for most obese and overweight people. 14,16 The classic twin adoption studies of Stunkard showed that both fatness and thinness were highly heritable and not influenced by the adopting family members' adiposity. 17 Numerous genetic studies since, in a variety of populations and using various measures of adiposity, have been consistent with those fundamental findings.…”
Section: Background and Aimsmentioning
confidence: 99%
“…The process is undergoing a revaluation, showing that obese individuals must accomplish appropriate steps to weight loss, under medical supervision (Gray et al, 2012).…”
Section: Introductionmentioning
confidence: 99%